Pengaruh Majalah Al-Imam (1906-1098) Singapura Terhadap Al-Munir (1911-1915) Padang - Sarwan Sarwan (Universitas Islam Negeri Imam Bonjol Padang, 2010)
Al-Imam (1906-1908) and Al-Munir (1911-1915) are the two magazines into the funnel of Young called the idea of Islamic reform in the archipelago. Relations between the two magazines can be traced through several ways, including through the characters involved in it, a similar form, contents and intellectual discourse.